The effect of ph and biomass concentration on lead (Pb) adsorption by Aspergillus niger from simulated waste water - David, A/L Joseph @ Dave (2008)
Heavy metals released by a number of industrial processes are major pollutants in marine, ground, industrial and even treated wastewaters. Lead is widely used in many industrial applications such as storage battery manufacturing, printing, pigments, fuels, photographic materials and explosive manufacturing. Lead is highly toxic as its presence in drinking water above the permissible limit (5 ng/mL) causes adverse health effects such as anemia, encephalopathy, hepatitis and nephritic syndrome. Conventionally, the following methods are employed for the removal of heavy metals from effluents such as oxidation and reduction, precipitation, filtration, electrochemical treatment, evaporation. The alternative method is discovered which is biosorption, refers to a physic-chemical binding of metal ions to biomass. It can be considered as an alternative technology for industrial wastewater treatment, The biosorption rate largely depends on parameters such as pH, initial biomass concentration and temperature. In this study, the biosorption of lead (Pb2+) from simulated waste water using Aspergillus niger was investigated. The biosorption process was carried out in a shake flask at different initial pH and biomass concentration. Results from experiment shows, among the different initial pH used, percentage of biosorption was highest is at pH 4.0 (77.99%) and for the experiment conducted at different initial biomass concentration, the highest percent of biosorption was obtained by using 20mg/l (40.58%) biomass. From the results also, it was observed that, the percentage of biosorption is directly proportional to the biomass concentration.Author